The Resolution of Intestinal Inflammation: The Peace-Keeper’s Perspective - Onali, Sara (Cells, 2019)
The uncontrolled activation of the immune system toward antigens contained in the gut lumen in genetically predisposed subjects is believed to be the leading cause of inflammatory bowel disease (IBD). Two not mutually exclusive hypotheses can explain the pathogenic process leading to IBD. The first and mostly explored hypothesis states that the loss of tolerance toward gut microbiota antigens generates an aberrant inflammatory response that is perpetuated by continuous and unavoidable exposure to the triggering antigens. However, the discovery that the resolution of inflammation is not the mere consequence of clearing inflammatory triggers and diluting pro-inflammatory factors, but rather an active process in which molecular and cellular elements are involved, implies that a defect in the pro-resolving mechanisms might cause chronic inflammation in different immune-mediated diseases, including IBD. Here we review data on pro-resolving and counter-regulatory mechanisms involved in the resolution of inflammation, aiming to identify their possible involvement in the pathogenesis of IBD.